Peran Manajemen Sumber Daya Manusia Dalam Meningkatkan Pendapatan Bumdes di Desa Belawae Kabupaten Sidenreng Rappang - Kori Hartono; Abdul Kadir; Muzakkir; Faisal (Precise Journal of Economic, 2025)
This study examines the role of human resource management in increasing the revenue of Village-Owned Enterprises (BUMDes) in Belawae Village, Sidenreng Rappang Regency. The research background is based on the importance of optimizing human resources in BUMDes management to strengthen the village economy. The purpose of this study is to analyze the extent to which human resource management functions such as planning, training, and supervision contribute to increasing BUMDes revenue. The research method used is a descriptive quantitative approach, with data collection techniques using questionnaires, interviews, and observations of all 12 BUMDes administrators (saturated sample). Data were analyzed using frequency tables and percentage calculations. The results indicate that effective human resource management, including collaboration between the village government and BUMDes administrators, has a positive impact on increasing income and community welfare. The implications of this study emphasize the importance of ongoing training, improving administrator competency, and community empowerment strategies in promoting village economic independence by optimizing the role of BUMDes..